Expansion and innovation in auxin signaling: where do we grow from here? - Ramos Báez, Román (Development, 2021)
The phytohormone auxin plays a role in almost all growth and developmental responses. The primary mechanism of auxin action involves the regulation of transcription via a core signaling pathway comprising proteins belonging to three classes: receptors, co-receptor/co-repressors and transcription factors. Recent studies have revealed that auxin signaling can be traced back at least as far as the transition to land. Moreover, studies in flowering plants have highlighted how expansion of the gene families encoding auxin components is tied to functional diversification. As we review here, these studies paint a picture of auxin signaling evolution as a driver of innovation.